Reconfigurable computing: architectures, tools, and applications : 10th International Symposium, ARC 2014, Vilamoura, Portugal, April 14-16, 2014. Proceedings - Santambrogio, Marco Domenico; Cardoso, Joao M. P.; Bertels, Koen; Goehringer, Diana (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed conference proceedings of the 10th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2014, held in Vilamoura, Portugal, in April 2014. The 16 revised full papers presented together with 17 short papers and 6 special session papers were carefully reviewed and selected from 57 submissions. The topics covered are applications; methods, frameworks and OS for debug, over-clocking, and relocation; memory architectures; methodologies and tools; and architectures.